Lagrangean decompositions for the unconstrained binary quadratic programming problem - Mauri, Geraldo Regis; Lorena, Luiz Antonio Nogueira (International transactions in operational research, 2011)
The unconstrained binary quadratic programming problem (QP) is a classical non‐linear problem of optimizing a quadratic objective by a suitable choice of binary decision variables. This paper proposes new Lagrangean decompositions to find bounds for QP. The methods presented treat a mixed binary linear version (LQP) of QP with constraints represented by a graph. This graph is partitioned into clusters of vertices forming a dual problem that is solved by a subgradient algorithm. The subproblems formed by the generated subgraphs are solved by CPLEX. Computational experiments consider a data set formed by several difficult instances with different features. The results show the efficiency of the proposed methods over traditional Lagrangean relaxations and other methods found in the literature.